MUHAMMAD SHAHRUR’S THEORY OF LIMITS IN ISLAMIC LEGAL REASONING: AN EPISTEMOLOGY AND APLICATION IN ISLAMIC FAMILY LAW - Ahmad Muhtar; Israwati Sibua; Amran Nani; Mujiburrahman Kautjil; Safri Nyong (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2026)
The “Limit Theory” (Nazhariyyah al-Hudud) was developed by Muhammad Syahrur as a response to the rigidity of classical Islamic jurisprudence, which is considered less capable of addressing contemporary social changes. This study examines Syahrur’s Limit Theory as a contemporary approach to Islamic legal reasoning (istinbath), focusing on its epistemological foundations, six geometric-typological patterns, and its application in Islamic family law. The research employs a qualitative library research method using a descriptive-analytical approach based on Syahrur’s principal works, especially al-Kitab wa al-Qur'an: Qira'ah Mu'ashirah, supported by relevant recent literature. The findings show that the Limit Theory categorizes legal rulings into six boundary models, including the minimum limit (al-hadd al-adna) and the maximum limit (al-hadd al-a'la), each representing a distinct framework for legal interpretation. Within these boundaries, Muslims are encouraged to exercise ijtihad in responding to changing social realities while remaining faithful to the principles of the Qur’an. The theory offers a flexible method for interpreting Islamic law, particularly in issues of inheritance and polygamy, by balancing textual authority with contextual justice. Syahrur’s approach contributes to the reconstruction of Islamic legal methodology, making it more responsive to contemporary challenges. However, it also remains controversial, especially among scholars who criticize its linguistic approach and its departure from established principles of classical Islamic jurisprudence. This study concludes that the Limit Theory should be understood as an alternative methodology for Islamic legal reform that deserves critical evaluation rather than unconditional acceptance.